Reforming Labor Legislation of the Belarus Republic: some problems - Evgenia Vladimirovna Motina; Samvel Igorevich Voskanyan (Сибирское юридическое обозрение, 2012)
Several directions of reforming the Belarusian labor legislation are considered in this article, taking into account so urgent politics of flexicurity. For that reason causes of giving flexibility to legal regulation of employment agreement termination are explored. The conclusion is made about the necessity of taking into account the objective criteria of differentiation by determining the specifics of separate employers' categories in the situation of labor relations termination.